Novel compound heterozygous OBSCN variants in Chinese children with congenital pulmonary airway malformation - Jiali Xu; Siyu Ma; Zhaocong Yang; Yang Xu; Jirong Qi; Min Da; Xuming Mo (Italian Journal of Pediatrics)
Abstract Background Congenital pulmonary airway malformation (CPAM) belongs to rare lung abnormalities which may result in poor lung development outcomes. However, the etiology of CPAM has not been well described. Methods In this study, whole-exome sequencing (WES) technology was used to sequence 9 CPAM families to screen the pathogenic genes and their mutations for CPAM. Sanger sequencing was performed for verify the functions of these mutations. Results We found compound heterozygous mutations in OBSCN gene in two patients with CPAM: one with p.G8837A mutation inherited from her father and p.G1126S mutation inherited from her mother; the other with p.R5167W mutation inherited from his father and p.A7475T mutation inherited from his mother. Immunofluorescence results showed that the expression of OBSCN protein in the central lung tissue of CPAM patients was lower than that in the distal lung tissue of the lesion, and the expression of OBSCN protein was decreased in OBSCN mutated. We further explored the expression of OBSCN during mouse lung development, confirming that the gene mainly acts on the pseudoglandular stage. Conclusions The OBSCN gene may play a key role in pseudoglandular stage during mouse lung development. The mutation of OBSCN gene may play a role in promoting the occurrence of CPAM, providing a possible therapeutic target for clinical intervention of CPAM.